2021
DOI: 10.1038/s41598-021-93037-7
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization demands of walking modulate the vestibular contributions to gait

Abstract: Stable walking relies critically on motor responses to signals of head motion provided by the vestibular system, which are phase-dependent and modulated differently within each muscle. It is unclear, however, whether these vestibular contributions also vary according to the stability of the walking task. Here we investigate how vestibular signals influence muscles relevant for gait stability (medial gastrocnemius, gluteus medius and erector spinae)—as well as their net effect on ground reaction forces—while hu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 93 publications
11
51
2
Order By: Relevance
“…Other mechanisms are shifting the center of pressure under the stance foot (Reimann et al 2018;van Leeuwen et al 2021) and changing angular momentum around the CoM (Hof 2008;van den Bogaart et al 2020). The increase in EVS-erector spinae muscle coupling during narrow-base walking that we found previously (Magnani et al 2021), suggests that indeed angular momentum changes may play a larger role during narrowbase walking, as was also seen in behavioral studies (Bogaart et al 2021).…”
Section: Effects Of Walking Conditionsupporting
confidence: 71%
See 3 more Smart Citations
“…Other mechanisms are shifting the center of pressure under the stance foot (Reimann et al 2018;van Leeuwen et al 2021) and changing angular momentum around the CoM (Hof 2008;van den Bogaart et al 2020). The increase in EVS-erector spinae muscle coupling during narrow-base walking that we found previously (Magnani et al 2021), suggests that indeed angular momentum changes may play a larger role during narrowbase walking, as was also seen in behavioral studies (Bogaart et al 2021).…”
Section: Effects Of Walking Conditionsupporting
confidence: 71%
“…In line with this, vestibular evoked responses in ground reaction force and muscles activity are increased in magnitude when one is exposed to a postural threat (Horslen et al 2014;Naranjo et al 2015). In a recent study (Magnani et al 2021)., we showed that, compared to normal walking, mediolateral ground reaction forces were less coupled to vestibular stimulation when subjects were stabilized by means of elastic cords providing conservative forces to maintain the mediolateral position of the body CoM or when walking with wide steps.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…We focused on changes in timing of muscle activation by assessing the synergy activation profiles’ full width at half maximum (FWHM), reflecting activation duration, and Center of Activation (CoA), reflecting time of peak activation. We hypothesized that adaptations to narrow-base walking would be reflected in enhanced gait stability [ 39 ] and in more prolonged muscle activation. Furthermore, we hypothesized that training effects would transfer to gait as reflected in improved gait stability and narrow-base walking performance and activation profiles with less prolonged muscle activation.…”
Section: Introductionmentioning
confidence: 99%